Mixture for all-solid-state secondary battery, mix sheet for all-solid-state secondary battery and method for producing same, and all-solid-state secondary battery
By employing PTFE with a fine fiber structure and controlled shear force application, the manufacturing process for all-solid-state secondary batteries is optimized, addressing performance issues and reducing electrolyte deterioration, resulting in high-efficiency batteries.
Patent Information
- Application Number
- JP2022546326
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-01
- Filing Date
- 2021-08-31
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-08-31
AI Technical Summary
Existing methods for producing all-solid-state secondary batteries using polytetrafluoroethylene (PTFE) as a binder result in poor performance due to insufficient fibrillation, leading to electrolyte deterioration and reduced battery efficiency, particularly when solvents are used in the manufacturing process.
The use of PTFE with a fine fiber structure having a fibril diameter of 70 nm or less, achieved through controlled shear force application and rolling, eliminates the need for solvents and enhances the binding properties of the battery mixture, thereby reducing electrolyte deterioration and improving battery performance.
This approach results in an all-solid-state secondary battery mixture with improved ionic conductivity and reduced manufacturing burden, producing batteries with enhanced durability and efficiency.
Smart Images

Figure 0007602146000001 
Figure 0007602146000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a mixture for an all-solid-state secondary battery, a mixture sheet for an all-solid-state secondary battery and a method for producing the same, and an all-solid-state secondary battery. [Background technology]
[0002] In lithium ion secondary batteries, a sheet for all-solid-state secondary batteries is generally produced by coating and drying a slurry obtained by mixing an electrode active material and a conductive assistant with a binder and a solvent.
[0003] On the other hand, polytetrafluoroethylene resin is a polymer that easily becomes fibrillated, and it is sometimes used as a binder after being fibrillated.
[0004] Patent Document 1 discloses a method for producing an electrode in which a mixture containing an active material and a polytetrafluoroethylene mixed binder material is subjected to high shear treatment using a jet mill to fibrillate the polytetrafluoroethylene. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 2017-517862 Summary of the Invention [Problem to be solved by the invention]
[0006] The present disclosure has an object to provide a mixture for an all-solid-state secondary battery having good properties, a mixture sheet for an all-solid-state secondary battery containing the mixture, and an all-solid-state secondary battery using the sheet for an all-solid-state secondary battery. Another object of the present disclosure is to provide a method for producing a sheet for an all-solid-state secondary battery containing a polytetrafluoroethylene resin having a fine fibrous structure. [Means for solving the problem]
[0007] The present disclosure relates to a mixture for an all-solid-state secondary battery, comprising a solid electrolyte and a binder, The binder is polytetrafluoroethylene resin. The polytetrafluoroethylene resin is a mixture for all-solid-state secondary batteries, characterized by having a fibrous structure with a fibril diameter (median value) of 70 nm or less.
[0008] The mixture for an all-solid-state secondary battery is preferably for a lithium-ion all-solid-state secondary battery. The mixture for an all-solid-state secondary battery is preferably for a sulfide-based all-solid-state secondary battery.
[0009] The mixture for an all-solid-state secondary battery is a mixture for an all-solid-state secondary battery obtained by using a raw material composition containing a solid electrolyte and a binder, and the raw material composition preferably contains a binder that is a powdered polytetrafluoroethylene resin. It is preferable that the raw material composition does not substantially contain a liquid medium.
[0010] The powdered polytetrafluoroethylene resin preferably has a moisture content of 500 ppm or less. The powdered polytetrafluoroethylene resin preferably has a standard specific gravity of 2.11 to 2.20.
[0011] The powdered polytetrafluoroethylene resin preferably contains 50% by mass or more of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. The powdered polytetrafluoroethylene resin preferably contains 80% by mass or more of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more.
[0012] The present disclosure also relates to a mixture sheet for an all-solid-state secondary battery, comprising the above-mentioned mixture for an all-solid-state secondary battery.
[0013] The present disclosure relates to a process for producing a raw material composition including a solid electrolyte and a binder, the process comprising: (1) applying a shear force to the raw material composition while mixing the raw material composition; A step (2) of forming the mixture for an all-solid-state secondary battery obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture for an all-solid-state secondary battery obtained in the step (2) into a sheet. The present invention is also a method for producing a mixture sheet for an all-solid-state secondary battery, characterized in that the binder is a powdered polytetrafluoroethylene resin.
[0014] The present disclosure also relates to an all-solid-state secondary battery having the above-mentioned mixture sheet for an all-solid-state secondary battery. Effect of the Invention
[0015] In the present disclosure, a battery with less degradation of the solid electrolyte can be manufactured by using a polytetrafluoroethylene resin (PTFE) powder with low moisture content as a binder without using a solvent when forming a mixture sheet for an all-solid-state secondary battery. Furthermore, in the manufacturing method of the present disclosure, a mixture sheet for an all-solid-state secondary battery containing a polytetrafluoroethylene resin having a fine fiber structure can be manufactured, and since a slurry is not prepared, the burden of the manufacturing process can be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present disclosure will be described in detail below. The present disclosure provides a mixture for an all-solid-state secondary battery that can be suitably used in an all-solid-state secondary battery, and a mixture sheet containing the same. In the all-solid-state secondary battery mixture and the mixture sheet containing the same disclosed herein, PTFE is used as a binder. In the conventional all-solid-state secondary battery mixture, a resin that dissolves in a solvent, such as a copolymer of vinylidene fluoride and hexafluoropropylene, is used as a binder, and a method of preparing the all-solid-state secondary battery mixture by coating and drying a slurry containing the binder was common.
[0017] It is known that when shear stress is applied to PTFE in a particulate state, it easily becomes fibrillated. By utilizing this fibrillating property, PTFE can be used as a binder. In other words, fibrillated PTFE becomes entangled with other powder components, etc., and binds the powder components together, thereby acting as a binder when molding the powder components.
[0018] However, even when fibrillated PTFE is used as a binder, if the fibrillation is insufficient, good performance cannot be exhibited when used as a mixture for an all-solid-state secondary battery. In the present disclosure, this point has been examined, and by carrying out fine fibrillation processing so that PTFE has a fibrous structure with a fibril diameter (median value) of 70 nm or less, the fibrillated PTFE can reduce deterioration of the solid electrolyte as a binder for a mixture for an all-solid-state secondary battery and can exhibit good performance.
[0019] That is, the present disclosure has found that when PTFE is used as a binder, by making it have a fine fibrous structure, it is possible to obtain a mixture for an all-solid-state secondary battery having good properties and a mixture sheet containing the same, and has thereby completed the present disclosure.
[0020] The all-solid-state secondary battery mixture of the present disclosure is obtained by using a raw material composition containing an electrode active material and a binder, and the binder is preferably powdered PTFE. Since PTFE powder is used as the raw material instead of PTFE aqueous dispersion, there is little moisture derived from the raw material in the all-solid-state secondary battery mixture, and there is no problem caused by the presence of moisture, which has the advantage of improving the battery performance. In addition, the battery can be made to have excellent ion conductivity.
[0021] Furthermore, it is preferable that the raw material composition does not substantially contain a liquid medium. Thus, the all-solid-state secondary battery mixture of the present disclosure has the advantage of not using a solvent in the production. That is, in the conventional all-solid-state secondary battery mixture forming method, a solvent in which a binder is dissolved is used to prepare a slurry in which powders, which are the all-solid-state secondary battery mixture components, are dispersed, and the slurry is applied and dried to prepare an all-solid-state secondary battery mixture sheet. In this case, a solvent that dissolves the binder is used. However, the solvents that can dissolve the binder resins that have been commonly used in the past are limited to specific solvents such as butyl butyrate, and these also deteriorate the solid electrolyte and cause a decrease in battery performance. In addition, the binder resins that can be dissolved in low-polarity solvents such as heptane are very limited, and the flash point is low, making handling difficult.
[0022] The mixture for an all-solid-state secondary battery disclosed herein has, as a component, PTFE having a fibrous structure with a fibril diameter (median) of 70 nm or less. In the present disclosure, it is important that the fibril diameter (median) is 70 nm or less. In this way, PTFE with a small fibril diameter is present in the mixture for an all-solid-state secondary battery, and this acts to bind the powders of the components constituting the mixture for an all-solid-state secondary battery, thereby achieving the object of the present invention.
[0023] The fibril diameter (median value) is a value measured by the following method. (1) Using a scanning electron microscope (S-4800 type, manufactured by Hitachi, Ltd.), a magnified photograph (7000 times) of the composite sheet for an all-solid-state secondary battery is taken to obtain an image. (2) Draw two equally spaced horizontal lines on this image to divide it into thirds. (3) For all PTFE fibers on the upper straight line, measure the diameter at three points per PTFE fiber, and take the average value as the diameter of the PTFE fiber. The three measurement points are the intersection of the PTFE fiber with the straight line, and points shifted 0.5 μm above and below the intersection (excluding unfiberized PTFE primary particles). (4) Repeat step (3) above for all the PTFE fibers in the lower straight line. (5) The screen is moved 1 mm to the right from the first image, and another image is taken, and the diameter of the PTFE fiber is measured using the above (3) and (4). This process is repeated until the number of fibers measured exceeds 80. (6) The median value of the diameters of all the PTFE fibers measured above was taken as the fibril diameter.
[0024] The fibril diameter (median) is preferably 65 nm or less, more preferably 62 nm or less. If the fibrillation proceeds too much, flexibility tends to be lost. The lower limit is not particularly limited, but from the viewpoint of strength, it is preferably 15 nm or more, and more preferably 20 nm or more.
[0025] The method for obtaining PTFE having the above fibril diameter (median value) is not particularly limited, but for example, A step (1) of applying a shear force to a raw material composition containing a solid electrolyte and a binder while mixing the raw material composition. A step (2) of forming the mixture for an all-solid-state secondary battery obtained by the step (1) into a bulk form; and The method includes a step (3) of rolling the bulk mixture for an all-solid-state secondary battery obtained in the step (2) into a sheet.
[0026] In such a method, for example, in step (1), by setting the mixing condition of the raw material composition to 1000 rpm or less, it is possible to promote fibrillation of PTFE while maintaining flexibility, and by controlling the applied shear stress, it is possible to set the PTFE fibril diameter (median) to 70 nm or less.
[0027] It is also preferable to have a step (4) after the step (3) in which the obtained rolled sheet is rolled under a larger load into a thinner sheet. It is also preferable to repeat the step (4). The fibril diameter can also be adjusted by crushing the obtained rolled sheet after step (3) or step (4), forming it into a bulk shape again, and rolling it into a sheet shape in step (5). Step (5) is preferably repeated, for example, from 1 to 12 times.
[0028] That is, by applying a shear force, the PTFE powder is fibrillated, and the fibrillated particles are entangled with powder components such as a solid electrolyte, thereby producing a mixture for an all-solid-state secondary battery. The production method will be described later.
[0029] In the present disclosure, the PTFE resin is not particularly limited, and may be a homopolymer or a copolymer that can be fibrillated. In the case of copolymers, examples of the fluorine atom-containing comonomer include chlorotrifluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroalkylethylene, and fluoroalkyl fluorovinyl ether.
[0030] The above-mentioned "PTFE powder" does not mean a dispersed state mixed with a liquid medium, but a solid state as a powder. By using such a state and using PTFE in the absence of a liquid medium to produce a mixture for an all-solid-state secondary battery, the object of the present disclosure can be suitably achieved.
[0031] The powdered PTFE used as a raw material for preparing the mixture for an all-solid-state secondary battery of the present disclosure preferably has a moisture content of 500 ppm or less. A moisture content of 500 ppm or less is preferable in terms of reducing deterioration of the solid electrolyte. The water content is more preferably 300 ppm or less.
[0032] The powdered PTFE used as a raw material for preparing the mixture for an all-solid-state secondary battery of the present disclosure preferably has a standard specific gravity of 2.11 to 2.20. The standard specific gravity being within this range is advantageous in that an electrode mixture sheet with high strength can be produced. The lower limit of the standard specific gravity is more preferably 2.12 or more. The upper limit of the standard specific gravity is more preferably 2.19 or less, and even more preferably 2.18 or less.
[0033] Standard specific gravity (SSG) is measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0034] The powdered PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, there is an advantage that a composite sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a composite sheet with lower resistance and excellent toughness can be obtained.
[0035] The lower limit of the secondary particle diameter of the powdered PTFE is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0036] The powdered PTFE has an average primary particle size of preferably 150 nm or more, more preferably 180 nm or more, even more preferably 210 nm or more, and particularly preferably 220 nm or more, since this allows the electrode mixture sheet to have higher strength and excellent homogeneity. The larger the average primary particle diameter of PTFE, the more suppressed the increase in extrusion pressure when extrusion molding is performed using the powder, and the better the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization process, it is preferably 350 nm.
[0037] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.
[0038] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may be, for example, polytetrafluoroethylene that contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in the particle.The modified polytetrafluoroethylene may be, for example, the polytetrafluoroethylene described in JP-A-2005-527652.
[0039] Powdered PTFE that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method, for example, by following the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0040] In the present disclosure, the lower limit of the binder content in the all-solid-state secondary battery mixture is preferably 0.2 mass% or more, more preferably 0.3 mass% or more. It is even more preferable that it exceeds 1.0 mass%. The upper limit of the binder content in the all-solid-state secondary battery mixture is preferably 10 mass% or less, more preferably 6.0 mass% or less. If the binder is within the above range, it is possible to mold a sheet that is self-supporting and has excellent handleability while suppressing an increase in electrode resistance.
[0041] The solid electrolyte used in the binder for all-solid-state secondary batteries of the present disclosure may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, it has the advantage of being flexible.
[0042] The above sulfide-based solid electrolyte is not particularly limited, and includes Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 Si 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4 (x = 0.6 to 0.8), Li 4+y Ge 1-y Ga y S4 (y = 0.2 to 0.3), LiPSCl, LiCl, Li 7-x-2y PS 6-x-y Cl x (0.8 ≦ x ≦ 1.7, 0 < y ≦ -0.25x + 0.5), etc., or a mixture of two or more thereof can be used.
[0043] The above sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid battery using lithium ions as carriers, and is particularly preferable in terms of an electrochemical device having a high energy density.
[0044] The above oxide-based solid electrolyte is preferably a compound that contains oxygen atoms (O), has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulation.
[0045] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (However, 1≦xd≦3, 0≦yd≦ 2 , 0≦zd≦2, 0≦ad≦ 2 , 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O12 , LiPO (4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 Examples of suitable ceramic materials include LLZ (LLZ-based ceramic materials). Ceramic materials in which element substitution has been performed on LLZ are also known. For example, LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) has been performed on LLZ are also known. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON in which part of the oxygen in lithium phosphate has been replaced with nitrogen, LiPOD, etc. 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc.) can also be preferably used. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.
[0046] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0047] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure, which is particularly preferred in terms of good Li-ion conductivity. Oxides with a crystalline structure include perovskite type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, etc.), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the NASICON type is preferred.
[0048] The volume average particle diameter of the oxide-based solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, and more preferably 0.03 μm or more. The upper limit is preferably 100 μm or less, and more preferably 50 μm or less. The average particle diameter of the oxide-based solid electrolyte particles is measured by the following procedure. The oxide-based solid electrolyte particles are diluted and adjusted to a 1 mass% dispersion in a 20 ml sample bottle using water (heptane in the case of a substance unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasonic waves for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is taken 50 times using a laser diffraction / scattering type particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C using a measurement quartz cell to obtain the volume average particle diameter. For other detailed conditions, etc., refer to the description of JISZ8828:2013 "Particle size analysis - dynamic light scattering method" as necessary. Five samples are prepared for each level and the average value is adopted.
[0049] The mixture for an all-solid-state secondary battery of the present disclosure is particularly suitable for a lithium-ion all-solid-state secondary battery. In addition, it is suitable for sulfide-based all-solid-state secondary batteries. When used in an all-solid-state secondary battery, the mixture for an all-solid-state secondary battery of the present disclosure is usually used in the form of a sheet.
[0050] The mixture sheet for an all-solid-state secondary battery of the present disclosure can be used as a positive electrode sheet or a negative electrode sheet. It can also be used as a sheet for a solid electrolyte layer. Of these, when used as an electrode sheet, it further contains active material particles. The active material particles can be a positive electrode active material or a negative electrode active material. The sheet for an all-solid-state secondary battery of the present disclosure can be more suitably used as a positive electrode sheet using a positive electrode active material. When used as an electrode sheet, it may contain a conductive assistant as necessary.
[0051] The electrode active material, the conductive assistant, etc. will be described below.
[0052] (electrode active material) When the all-solid-state secondary battery mixture sheet of the present disclosure is used as a positive electrode sheet, a positive electrode active material is blended into the all-solid-state secondary battery mixture sheet. The positive electrode active material can be a positive electrode active material known as a positive electrode active material for solid-state batteries. In particular, it is preferable to use a positive electrode active material capable of absorbing and releasing lithium ions. The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but is preferably, for example, a material containing an alkali metal and at least one transition metal, specific examples of which include an alkali metal-containing transition metal composite oxide, an alkali metal-containing transition metal phosphate compound, a conductive polymer, and the like. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal composite oxide that produces high voltage. The alkali metal ion may be a lithium ion, a sodium ion, a potassium ion, or the like. In a preferred embodiment, the alkali metal ion may be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0053] Examples of the alkali metal-containing transition metal composite oxide include: Formula:M a Mn 2-b M 1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 CO2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge) In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0054] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like are preferred, and a compound represented by the following general formula (3) is preferred. MNi h Co i Mn j M 5 k O2(3) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.
[0055] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following formula (4): M e M 4 f (PO4) g (4) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3) are included. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.
[0056] The transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these compounds has been substituted with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound preferably has an olivine structure.
[0057] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3 (wherein M is at least one metal selected from the group consisting of Li, Na, and K), etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 A positive electrode active material such as O2 is preferable in that the crystal structure does not collapse when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or more. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the above-mentioned positive electrode active material is preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.
[0058] Other positive electrode active materials include M2MnO3 and MM 6 O2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K; M 6 Also included are solid solution materials with transition metals such as Co, Ni, Mn, and Fe.
[0059] The solid solution material may be, for example, a material represented by the general formula Mx[Mn(1-y) M 7 y O z is an alkali metal manganese oxide represented by the formula. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and contains, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 A manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as Li2MnO3 is preferable because it can provide an alkali metal ion secondary battery having a high energy density.
[0060] In addition, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferable to mix and use the above positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and still more preferably 0.5% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and still more preferably 5% by mass or less, based on the total of the above positive electrode active material and lithium phosphate.
[0061] Examples of the conductive polymer include p-doped conductive polymers and n-doped conductive polymers. Examples of the conductive polymer include polyacetylene-based, polyphenylene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, and the like.
[0062] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.
[0063] These surface-attaching substances can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending in a solvent, impregnating or adding to the positive electrode active material, and then drying, a method of dissolving or suspending a surface-attaching substance precursor in a solvent, impregnating and adding to the positive electrode active material, and then reacting by heating, a method of adding to a positive electrode active material precursor and simultaneously baking, etc. When carbon is attached, a method of mechanically attaching carbonaceous material in the form of, for example, activated carbon, etc., afterwards can also be used.
[0064] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more, and preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less, by mass relative to the positive electrode active material. The surface-attached substance can suppress the oxidation reaction of the solid electrolyte on the surface of the positive electrode active material, thereby improving the battery life. If the amount of attachment is too small, the effect is not fully manifested, and if it is too large, the ingress and egress of lithium ions is hindered, increasing the resistance. There are cases.
[0065] The shape of the particles of the positive electrode active material may be any of the conventional shapes such as block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles.
[0066] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3More preferably, 1.0 g / cm 3 That is all. If the tap density of the positive electrode active material is below the lower limit, the amount of dispersion medium required during the formation of the positive electrode active material layer increases, and the amount of conductive material and binder required also increases, restricting the filling rate of the positive electrode active material in the positive electrode active material layer and possibly restricting the battery capacity. By using a complex oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally, the higher the tap density, the better, and there is no particular upper limit. However, if the tap density is too high, the diffusion of lithium ions in the positive electrode active material layer using the solid electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated, so the upper limit is preferably 4.0 g / cm. 3 Less than or equal to 3.7 g / cm 3 More preferably, 3.5 g / cm 3 The following is the result. In the present disclosure, the tap density is the powder packing density (tap density) g / cm when 5 to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and tapped 200 times with a stroke of about 20 mm. 3 is required.
[0067] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when primary particles are aggregated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, and most preferably 1.0 μm or more, and is preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, and most preferably 22 μm or less. If it is below the lower limit, a high tap density product may not be obtained, and if it exceeds the upper limit, it may take time for lithium to diffuse within the particles, resulting in a decrease in battery performance, or problems such as streaking may occur when preparing the positive electrode of a battery, that is, when the active material, conductive material, binder, etc. are slurried with a solvent and applied in a thin film. Here, by mixing two or more types of the above positive electrode active materials having different median diameters d50, the filling property during the preparation of the positive electrode can be further improved.
[0068] In the present disclosure, the median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% by mass sodium hexametaphosphate aqueous solution is used as the dispersion medium for the measurement, and the measurement is performed after ultrasonic dispersion for 5 minutes with a measurement refractive index set to 1.24.
[0069] In the case where the primary particles are aggregated to form secondary particles, the average primary particle diameter of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which may adversely affect the powder packing property or greatly reduce the specific surface area, and therefore the battery performance such as output characteristics may be likely to decrease. On the other hand, if the lower limit is exceeded, problems such as poor reversibility of charge and discharge may occur due to underdeveloped crystals.
[0070] In the present disclosure, the average primary particle diameter of the positive electrode active material is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest intercept value of a horizontal line at the left and right boundaries of the primary particles is obtained for any 50 primary particles, and the average value is calculated.
[0071] The BET specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, whereas if it is larger, it is difficult to increase the tap density, and problems may easily occur in the application property when forming the positive electrode active material layer.
[0072] In the present disclosure, the BET specific surface area is defined as a value measured by a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.) using a nitrogen adsorption BET single-point method based on a gas flow method, after pre-drying a sample at 150°C for 30 minutes under a nitrogen flow and using a nitrogen-helium mixed gas precisely adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.
[0073] When the secondary battery of the present disclosure is used as a large-scale lithium-ion secondary battery for hybrid automobiles or distributed power sources, high output is required, so that the particles of the positive electrode active material are preferably mainly secondary particles. The particles of the positive electrode active material preferably contain 0.5 to 7.0 volume % of fine particles having an average secondary particle size of 40 μm or less and an average primary particle size of 1 μm or less. By containing fine particles having an average primary particle size of 1 μm or less, the contact area with the solid electrolyte is increased, and the diffusion of lithium ions between the sheet for all-solid-state secondary batteries and the solid electrolyte can be made faster, resulting in improved output performance of the battery.
[0074] The manufacturing method of the positive electrode active material is a general method for manufacturing inorganic compounds.In particular, various methods can be considered for making spherical or elliptical active materials, for example, the raw material of transition metal is dissolved or crushed and dispersed in a solvent such as water, and the pH is adjusted while stirring to make and recover spherical precursors, which are dried as necessary, and then LiOH, Li2CO3, LiNO3, or other Li sources are added and calcined at high temperature to obtain active materials.
[0075] For the production of the positive electrode, the positive electrode active material may be used alone, or two or more kinds of different compositions may be used in any combination or ratio. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.
[0076] The content of the positive electrode active material in the positive electrode mixture is preferably 50 to 99.5% by mass, and more preferably 80 to 99% by mass, in view of high battery capacity. The content of the positive electrode active material is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. The upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode mixture is low, the electric capacity may be insufficient. Conversely, if the content is too high, the strength of the positive electrode may be insufficient.
[0077] The negative electrode active material is not particularly limited, and examples thereof include those containing carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; Li4Ti5O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.
[0078] In order to increase the capacity of the resulting all-solid-state secondary battery mixture sheet, the content of the negative electrode active material is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more in the all-solid-state secondary battery mixture sheet, and the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less.
[0079] (Conductive assistant) Any known conductive material can be used as the conductive assistant. Specific examples include metal materials such as copper and nickel, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF. These may be used alone or in any combination and ratio of two or more.
[0080] The conductive assistant is used in such a manner that it is contained in the electrode active material layer in an amount of usually 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less. If the content is lower than this range, the conductivity may be insufficient. Conversely, if the content is higher than this range, the battery capacity may decrease.
[0081] (Other Ingredients) The mixture sheet for an all-solid-state secondary battery may further contain a thermoplastic resin. Examples of the thermoplastic resin include vinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polyethylene oxide, etc. One type may be used alone, or two or more types may be used in any combination and ratio.
[0082] The ratio of the thermoplastic resin to the electrode active material is usually 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and usually 3.0% by mass or less, preferably 2.5% by mass or less, more preferably 2.0% by mass or less. The addition of the thermoplastic resin can improve the mechanical strength of the electrode. If the ratio exceeds this range, the ratio of the active material in the electrode mixture decreases, which may cause problems such as a decrease in the battery capacity or an increase in the resistance between the active materials.
[0083] In the all-solid-state secondary battery mix sheet of the present disclosure, the content of the binder is usually 0.1 mass% or more, preferably 0.3 mass% or more, more preferably 0.5 mass% or more, and usually 80 mass% or less, preferably 60 mass% or less, more preferably 40 mass% or less, and most preferably 20 mass% or less, as the ratio of the binder in the all-solid-state secondary battery mix sheet. If the ratio of the binder is too low, the active material cannot be sufficiently held in the all-solid-state secondary battery mix sheet, and the mechanical strength of the all-solid-state secondary battery mix sheet may be insufficient, which may deteriorate the battery performance such as cycle characteristics. On the other hand, if the ratio is too high, it may lead to a decrease in battery capacity and conductivity.
[0084] (Manufacturing method) The production method of the mixture sheet for an all-solid-state secondary battery according to the present disclosure is not limited, but an example of a specific production method will be described below. The mixture sheet for an all-solid-state secondary battery according to the present disclosure is A step (1) of applying a shear force to a raw material composition containing a solid electrolyte and a binder while mixing the raw material composition. A step (2) of forming the mixture for an all-solid-state secondary battery obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture for an all-solid-state secondary battery obtained in the step (2) into a sheet. The electrode mixture sheet for a secondary battery having the above structure can be obtained by the method for producing the electrode mixture sheet for a secondary battery having the above structure.
[0085] At the stage where the raw material composition is mixed and shear force is applied in the above step (1), the resulting mixture for an all-solid-state secondary battery is present in a formless state in which the solid electrolyte, binder, etc. are simply mixed together. Specific mixing methods include mixing methods using a W-type mixer, V-type mixer, drum-type mixer, ribbon mixer, conical screw-type mixer, single-shape kneader, twin-shape kneader, mix muller, stirring mixer, planetary mixer, etc.
[0086] In the above step (1), the mixing conditions may be appropriately set by the number of revolutions and the mixing time. For example, the number of revolutions is preferably 1000 rpm or less. It is preferably 10 rpm or more, more preferably 15 rpm or more, and even more preferably 20 rpm or more, and is preferably 900 rpm or less, more preferably 800 rpm or less, and even more preferably 700 rpm. If the number of revolutions is less than the above range, mixing takes a long time, which affects productivity. If the number of revolutions is more than the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with inferior strength.
[0087] In the above step (2), forming into a bulk form means forming the mixture for an all-solid-state secondary battery into one mass. Specific methods for forming the material into a bulk form include extrusion molding, press molding, and the like. In addition, the term "bulk" does not specify a particular shape, and may refer to a state in which the material is in the form of a single mass, including rods, sheets, spheres, cubes, etc. The size of the mass is preferably such that the diameter or the smallest side of the cross section is 10,000 μm or more, more preferably 20,000 μm or more.
[0088] Specific examples of the rolling method in the above step (3) include rolling methods using a roll press, a plate press, a calendar roll machine, or the like.
[0089] It is also preferable to have a step (4) after step (3) in which a larger load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also preferable to repeat step (4). In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (4) is preferably from 2 to 10, and more preferably from 3 to 9. A specific rolling method includes, for example, a method in which a rolled sheet is passed between two or more rotating rolls to process it into a thinner sheet.
[0090] From the viewpoint of adjusting the fibril diameter, it is also preferable to have a step (5) after step (3) or step (4) in which the rolled sheet is roughly crushed, then formed into a bulk shape again, and rolled into a sheet. It is also preferable to repeat step (5). The number of times of step (5) is preferably 1 to 12 times, more preferably 2 to 11 times.
[0091] In step (5), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include folding the rolled sheet, forming it into a rod or thin sheet shape, chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (3) or step (4) into a different shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.
[0092] Furthermore, step (4) may be carried out after step (5), or may be carried out repeatedly. Moreover, uniaxial or biaxial stretching may be carried out in steps (2), (3), (4) and (5). The fibril diameter (median) can also be adjusted by the degree of crushing in step (5).
[0093] In the above steps (3), (4) or (5), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% or less, and even more preferably 50% or less. If the rolling ratio is below the above range, the number of rolling times increases and it takes time, which affects productivity. If the rolling ratio is above the above range, fibrillation may proceed excessively, resulting in an electrode mixture sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after rolling to the thickness before rolling. The sample before rolling may be a bulk raw material composition or a sheet-like raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling.
[0094] As described above, the PTFE powder is fibrillated by applying a shear force. In order to obtain a fibrous structure with a fibril diameter (median) of 70 nm or less, excessive shear stress may promote fibrillation too much, resulting in loss of flexibility. In addition, weak shear stress may not be sufficient in terms of strength. For this reason, by performing the steps of applying an appropriate shear stress to the PTFE during mixing or rolling to promote fibrillation, and rolling the resin to stretch it into a sheet shape within the above range, it is possible to obtain a fibrous structure with a fibril diameter (median) of 70 nm.
[0095] As described above, the mixture sheet for an all-solid-state secondary battery according to the present disclosure can be either a positive electrode sheet or a negative electrode sheet. When the mixture sheet for a positive electrode or a negative electrode is used, a positive electrode active material or a negative electrode active material may be mixed together with a solid electrolyte and a binder in the production of the mixture sheet for an all-solid-state secondary battery.
[0096] The positive electrode and the negative electrode will be described below. (positive electrode) In the present disclosure, the positive electrode is preferably composed of a current collector and the above-mentioned positive electrode sheet. Examples of the material for the positive electrode current collector include metals such as aluminum, titanium, tantalum, stainless steel, and nickel, or metal materials such as alloys thereof, and carbon materials such as carbon cloth and carbon paper. Among these, metal materials, particularly aluminum or its alloys, are preferred.
[0097] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foamed metal, etc. in the case of a metal material, or carbon plate, carbon thin film, carbon cylinder, etc. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is arbitrary, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and is usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling properties may be impaired.
[0098] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode mixture sheet. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.
[0099] The positive electrode may be produced by a conventional method, for example, a method in which the positive electrode sheet and a current collector are laminated with an adhesive therebetween, and then dried.
[0100] The density of the positive electrode sheet is preferably 2.0 g / cm 3 More preferably, 2.1 g / cm 3 More preferably, 2.3 g / cm 3 More preferably, it is 4.0 g / cm 3 Less than or equal to 3.9 g / cm 3 More preferably, 3.8 g / cm 3 The range is as follows. If it exceeds this range, the conductivity between the active materials decreases, the battery resistance increases, and high output may not be obtained. If it falls below this range, the content of the hard and brittle active materials may be low, resulting in a battery with low capacity.
[0101] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture sheet minus the thickness of the current collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit for one side of the current collector, and is also preferably 500 μm or less, more preferably 450 μm or less.
[0102] The positive electrode may have a surface to which a substance of a different composition is attached, such as oxides, such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates, such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates, such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.
[0103] (Negative electrode) In the present disclosure, the negative electrode is preferably composed of a current collector and the above-mentioned negative electrode sheet. Examples of the material for the negative electrode current collector include metals such as copper, nickel, titanium, tantalum, and stainless steel, and metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among these, metal materials, particularly copper, nickel, and alloys thereof are preferred.
[0104] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.
[0105] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned negative electrode sheet and a current collector are laminated with an adhesive therebetween, and then dried.
[0106] The density of the negative electrode sheet is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the solid electrolyte to the vicinity of the interface between the current collector and the active material decreases, and the charge / discharge characteristics, particularly at high current density, may decrease, making it impossible to obtain high output. If the range is exceeded, the conductivity between the active materials decreases, the battery resistance increases, and it may not be possible to obtain high output.
[0107] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the composite sheet minus the thickness of the metal foil of the current collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit for one side of the current collector, and is also preferably 500 μm or less, more preferably 450 μm or less.
[0108] (All-solid-state secondary battery) The present disclosure also relates to an all-solid-state secondary battery using the above-mentioned mixture sheet for an all-solid-state secondary battery. The all-solid-state secondary battery is preferably a lithium ion battery. Also, the all-solid-state secondary battery is preferably a sulfide-based all-solid-state secondary battery. The all-solid-state secondary battery of the present disclosure is an all-solid-state secondary battery including a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and the positive electrode, the negative electrode, and the solid electrolyte layer contain the above-mentioned all-solid-state secondary battery mixture sheet of the present disclosure, that is, the positive electrode sheet, the negative electrode sheet, or the solid electrolyte layer sheet. Note that the all-solid-state secondary battery of the present disclosure may use a material other than the all-solid-state secondary battery mixture sheet of the present disclosure for a part of the positive electrode, the negative electrode, and the solid electrolyte layer.
[0109] The laminate structure of the all-solid-state secondary battery according to the present disclosure includes a positive electrode including a positive electrode sheet and a positive electrode current collector, a negative electrode including a negative electrode sheet and a negative electrode current collector, and a sulfide-based solid electrolyte layer sandwiched between the positive electrode and the negative electrode. The separator and battery case used in the all-solid-state secondary battery according to the present disclosure will be described in detail below.
[0110] (Separator) The all-solid-state secondary battery of the present disclosure may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.
[0111] (Battery design) The all-solid-state secondary battery of the present disclosure may further include a battery case. The shape of the battery case used in the present disclosure is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, sulfide-based solid battery electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.
[0112] In the method for producing the all-solid-state secondary battery of the present disclosure, for example, first, the positive electrode, the solid electrolyte layer sheet, and the negative electrode are laminated in this order and pressed to form an all-solid-state secondary battery. By using the mixture sheet for an all-solid-state secondary battery according to the present disclosure, an all-solid-state secondary battery can be manufactured with a small amount of moisture in the system, and an all-solid-state secondary battery having good performance can be obtained, which is preferable. EXAMPLES
[0113] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0114] [Preparation Example 1] When 367 g of TFE (35.6% by mass relative to the total polymerization amount of 1032 g of TFE) was consumed from the start of polymerization, an aqueous solution of 12.0 mg of hydroquinone dissolved in 20 ml of water as a radical scavenger was injected with TFE (concentration 4.0 ppm relative to the aqueous medium). The polymerization continued thereafter, and when the polymerization amount of TFE reached 1000 g from the start of polymerization, the supply of TFE was stopped, and the gas in the system was immediately released to normal pressure, the polymerization reaction was terminated, and an aqueous polytetrafluoroethylene dispersion (solid content 31.2% by mass) was obtained. The obtained aqueous polytetrafluoroethylene dispersion was diluted to a solid content concentration of 15%, and the polytetrafluoroethylene was coagulated by gently stirring in a vessel equipped with a stirrer in the presence of nitric acid. The coagulated polytetrafluoroethylene was separated and dried at 160 ° C. for 18 hours to obtain powdered PTFE-1.
[0115] [Preparation Example 2] Powdered PTFE-2 was prepared by referring to Example 3 of International Publication No. 2015-080291.
[0116] [Preparation Example 3] Powdered PTFE-3 was prepared with reference to Preparation Example 1 of WO 2012 / 086710.
[0117] [Preparation Example 4] Powdered PTFE-4 was prepared by referring to Preparation Example 1 of International Patent No. 2012-063622. The physical properties of the prepared PTFE are shown in Table 1.
[0118] [Table 1]
[0119] Example 1 The sulfide-based solid electrolyte (0.75Li2S·0.25P2S5) and powdered PTFE-1 were weighed and stirred in a mortar at 200 rpm for 1 hour to obtain a mixture. The powdered PTFE-1 was dried in a vacuum dryer at 50°C for 1 hour before use. The powdered PTFE was sieved in advance using a stainless steel sieve with 500 μm openings, and the powder remaining on the sieve was used. The mass ratio of the solid content was solid electrolyte:binder = 95:5. The resulting mixture was formed into a bulk form and rolled into a sheet. After that, the rolled sheet obtained earlier was folded in two to be crushed roughly, and then formed into a bulk shape again, and then rolled into a sheet shape using a metal roll on a flat plate, and this process of promoting fibrillation was repeated four times. After that, further rolling was performed to obtain a sheet-like solid electrolyte layer with a thickness of 500 μm. Furthermore, the sheet-like solid electrolyte layer was cut out, put into a press machine and rolled. Furthermore, a load of 5 kN was repeatedly applied to adjust the thickness. The gap was adjusted so that the final thickness of the solid electrolyte layer was 150 μm. The above operations were performed in an Ar glow box (dew point about -80 ° C.). The initial rolling rate was the largest, at 39%.
[0120] (Examples 2, 3, and 4) A solid electrolyte layer was produced in the same manner as in Example 1, except that the powdered PTFE shown in Table 2 was used.
[0121] Example 5 A solid electrolyte layer was produced in the same manner as in Example 1, except that the powdered PTFE shown in Table 2 was used without being sieved.
[0122] Comparative Example 1 The sulfide-based solid electrolyte (0.75Li2S·0.25P2S5) and the powdered PTFE shown in Table 2 were weighed out and stirred in a mortar at 200 rpm for 1 hour to obtain a mixture. The powdered PTFE was used after drying for 1 hour in a vacuum dryer at 50° C. The mass ratio of the solid content was solid electrolyte:binder=95:5. The resulting mixture was formed into a bulk form and rolled into a sheet. The rolled sheet obtained above was then folded in half to crush it into a coarse powder, and then formed into a bulk shape again. The process of promoting fibrillation by rolling the sheet using a metal roll on a flat plate was repeated four times. After that, further rolling was performed to obtain a sheet-shaped solid electrolyte layer with a thickness of 500 μm. Furthermore, the sheet-shaped solid electrolyte layer was cut out and placed in a press machine for rolling. Furthermore, a load of 8 kN was repeatedly applied to adjust the thickness. The gap was adjusted so that the final thickness of the solid electrolyte layer was 150 μm. The above operations were performed in an Ar glow box (dew point approximately -80°C). The initial rolling reduction rate was the largest, at 61%.
[0123] Comparative Example 2 Using the powdered PTFE shown in Table 2, and otherwise following the same procedures as in Comparative Example 1, a sheet-shaped solid electrolyte layer was produced.
[0124] (Reference example 1) A VDF:HFP copolymer was prepared as a binder, which was added to butyl butyrate (Kishida Chemical Co., Ltd.) and stirred with a mix rotor to prepare a binder solution. Here, the binder was included at 5 mass% with the entire binder solution being 100 mass%. A sulfide-based solid electrolyte (0.75Li2S·0.25P2S5) was added to the binder solution, and ultrasonic treatment was performed using an ultrasonic homogenizer to obtain a "slurry for solid electrolyte layer" in which the sulfide-based solid electrolyte and binder were dispersed. The solid content was set to a mass ratio of solid electrolyte: binder = 95:5. The solid content ratio of the finally obtained slurry was 68 mass%. The prepared electrolyte slurry was applied to a peelable substrate using a doctor blade and dried. Then, pressing was performed to obtain a solid electrolyte pellet with the same density as in Example 1. The above operation was performed in an Ar glow box (dew point about -80 ° C.).
[0125] Each test was carried out in the following manner. [Measurement of moisture content] The powdered PTFE was dried in a vacuum dryer at 50°C for 1 hour before use. The moisture content of the PTFE after vacuum drying was measured using a Karl Fischer moisture meter (ADP-511 / MKC-510N, manufactured by Kyoto Electronics Manufacturing Co., Ltd.) with a boat-type moisture vaporizer, and the moisture vaporized by heating to 210°C in the moisture vaporizer was measured. Nitrogen gas was flowed as the carrier gas at a flow rate of 200 mL / min, and the measurement time was 30 minutes. Chem-Aqua was used as the Karl Fischer reagent. The sample amount was 1.5 g.
[0126] [PTFE fibril diameter (median)] (1) Using a scanning electron microscope (S-4800, manufactured by Hitachi, Ltd.), a magnified photograph (7000x) of the sheet-shaped solid electrolyte layer is taken to obtain an image. (2) Draw two equally spaced horizontal lines on this image to divide it into thirds. (3) For all PTFE fibers on the straight line above, measure the diameter at three points per PTFE fiber, and take the average value as the diameter of the PTFE fiber. The three measurement points are the intersection of the PTFE fiber with the straight line, and points shifted 0.5 μm above and below the intersection (excluding unfiberized PTFE primary particles). (4) Repeat step (3) above for all the PTFE fibers in the lower straight line. (5) The screen is moved 1 mm to the right from the first image, and another image is taken, and the diameter of the PTFE fiber is measured using the above (3) and (4). This process is repeated until the number of fibers measured exceeds 80. (6) The median value of the diameters of all the PTFE fibers measured above was taken as the fibril diameter.
[0127] [Conductivity of solid electrolyte] The conductivity was measured by the following method. A gold electrode was prepared on the surface of the prepared solid electrolyte sheet by sputtering, and then punched out to a diameter of 10 mm. The sheet was sandwiched between stainless steel current collectors to prepare a measurement cell. The cell was subjected to AC impedance measurement in a frequency range of 0.1 Hz to 8 MHz using an impedance analyzer (Solatron Model 1260) in a dry argon atmosphere to determine the conductivity. The value of Comparative Example 1 was standardized as 100%.
[0128] [Flexibility evaluation] The solid electrolyte sheet thus prepared was cut into a test piece measuring 2 cm in length and 6 cm in width. After wrapping the test piece around a round bar with a diameter of 4 mm, the test piece was visually inspected and evaluated according to the following criteria. If no scratches or cracks were found, the test piece was evaluated as ○, and if cracks were found, the test piece was evaluated as ×.
[0129] [Strength measurement] Using a digital force gauge (IMADA ZTS-20N), measurements were taken on 4 mm wide rectangular electrode mixture test pieces at 100 mm / min. The chuck distance was 30 mm. Displacement was applied until breakage, and the maximum stress of the measured results was taken as the strength of each sample. The value of Comparative Example 1 was standardized as 100%.
[0130] The test results are shown in Table 2.
[0131] [Table 2]
[0132] The results in Table 2 show that the sheet-shaped solid electrolyte layers of the Examples have excellent physical properties. [Industrial Applicability]
[0133] The mixture for an all-solid-state secondary battery according to the present disclosure and the mixture sheet for an all-solid-state secondary battery containing the same can be used in the production of an all-solid-state secondary battery.
Claims
1. A mixture for an all-solid-state secondary battery containing a solid electrolyte and a binder, The binder is polytetrafluoroethylene resin. A mixture for an all-solid-state secondary battery, wherein the polytetrafluoroethylene resin has a fibrous structure with a fibril diameter (median value) of 70 nm or less.
2. The mixture for an all-solid-state secondary battery according to claim 1, which is for a lithium ion all-solid-state secondary battery.
3. The mixture for an all-solid-state secondary battery according to claim 1 or 2, which is for a sulfide-based all-solid-state secondary battery.
4. 2. The mixture for an all-solid-state secondary battery according to claim 1, obtained by using a raw material composition containing a solid electrolyte and a binder, 2. The mixture for an all-solid-state secondary battery according to claim 1, wherein the binder in the raw material composition is a powdered polytetrafluoroethylene resin.
5. The mixture for an all-solid-state secondary battery according to claim 4 , wherein the raw material composition does not substantially contain a liquid medium.
6. 6. The mixture for an all-solid-state secondary battery according to claim 4, wherein the powdered polytetrafluoroethylene resin has a moisture content of 500 ppm or less.
7. 7. The mixture for an all-solid-state secondary battery according to claim 4, 5 or 6, wherein the powdered polytetrafluoroethylene resin has a standard specific gravity of 2.12 to 2.
18.
8. 8. The mixture for an all-solid-state secondary battery according to claim 4, 5, 6 or 7, wherein the powdered polytetrafluoroethylene resin contains 50 mass % or more of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more.
9. 8. The mixture for an all-solid-state secondary battery according to claim 4, 5, 6 or 7, wherein the powdered polytetrafluoroethylene resin contains 80 mass % or more of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more.
10. A mixture sheet for an all-solid-state secondary battery comprising the mixture for an all-solid-state battery according to any one of claims 1 to 9.
11. An all-solid-state secondary battery comprising the mixture sheet for an all-solid-state secondary battery according to claim 10.
Citation Information
Patent Citations
Method of manufacturing electrode composite for secondary battery, electrode for secondary battery and secondary battery
JP2011258333A
Dry electrode for energy storage device and its manufacturing method
JP2017517862A
Method for producing a solid electrolyte membrane for an all-solid-state battery and solid electrolyte membrane produced by said method
JP2020509565A
Solid electrolyte, and preparation method therefor and application thereof
WO2019154438A1
Solid electrolyte composition, solid electrolyte-containing sheet, electrode sheet for all solid state secondary battery, and all solid state secondary battery
WO2020036055A1
